Sequence Diversity and Differences at the Highly Duplicated MHC-I Gene Reflect Viral Susceptibility in Sympatric Pinniped Species. (11th June 2022) - Gigliotti, Alayna K; Bowen, W Don; Hammill, Michael O; Puryear, Wendy B; Runstadler, Jonathan; Wenzel, Frederick W; Cammen, Kristina M
Abstract: Differences in disease susceptibility among species can result from rapid host–pathogen coevolution and differences in host species ecology that affect the strength and direction of natural selection. Among 2 sympatric pinniped species that differ in sociality and putative disease exposure, we investigate observed differences in susceptibility through an analysis of a highly variable, duplicated gene family involved in the vertebrate immune response. Using high-throughput amplicon sequencing, we characterize diversity at the 2 exons that encode the peptide binding region of the major histocompatibility complex class I ( MHC-I ) gene in harbor ( N = 60) and gray ( N = 90) seal populations from the Northwest Atlantic. Across species, we identified 106 full-length exon 2 and 103 exon 3 sequence variants and a minimum of 11 duplicated MHC-I loci. The sequence variants clustered in 15 supertypes defined by the physiochemical properties of the peptide binding region, including a putatively novel Northwest Atlantic MHC-I diversity sublineage. Trans-species polymorphisms, dN/dS ratios, and evidence of gene conversion among supertypes are consistent with balancing selection acting on this gene. High functional redundancy suggests particularly strong selection among gray seals at the novel Northwest Atlantic MHC-I diversity sublineage. At exon 2, harbor seals had a significantly greater number of variants per individual than gray seals, but fewer supertypes. Supertype richness and private supertypes are hypothesized to contribute to observed differences in disease resistance between species, as consistently, across the North Atlantic and many disease outbreaks, gray seals appear to be more resistant to respiratory viruses than harbor seals.